EP095/#856 Comparison of survival outcome of open, total laparoscopic, and laparoscopy-assisted vaginal radical hysterectomy for stage IB2 cervical cancer patients: a multicenter retrospective study. (4th December 2022) - Yoon, Hyung Joon; Kim, Eun Taeg; Jeong, Ha Eun; Suh, Dong Soo
Abstract : Objectives: The aim of this study was to compare survival outcomes of three different radical hysterectomy (RH) types, namely total abdominal radical hysterectomy(TARH), total laparoscopic radical hysterectomy(TLRH), and laparoscopy-assisted radical vaginal hysterectomy(LARVH), in patients with FIGO stage IB2 cervical cancer. Methods: The study cohort was retrospectively recruited from three institutions in Korea—two Pusan National University Hospital (Pusan and Yangsan) and Ulsan University Hospital—between 2010 and 2017. Patients with stage IB2 cervical cancer were included and classified into TARH, TLRH, and LARVH treatment groups. Survival outcomes were estimated by the Kaplan-Meier and compared with the log-rank test. Cox proportional hazards models were fit to estimate the independent association of RH technique with outcome. Results: 194 patients were included in this study. No significant difference was found in the clinicopathological characteristics in each group. On comparing survival outcomes with TARH, both TLRH and LARVH showed no significant difference in terms of five-year overall survival (OS) (TARH vs. TLRH, p=0.121 and TARH vs. LARVH, p=0.436). Conversely, compared to the TARH group, five-year progression-free survival (PFS) was significantly worse in the TLRH group (p=0.034) but not in the LARVH group (p = 0.288). Multivariate analysis showed that TLRH surgical approach (HR, 3.232; 95% CI, 1.24–8.44; p=0.017) was an independent prognostic factor for PFS in patients with IB2 cervical cancer. Conclusions: Our study suggests that in patients with FIGO stage IB2 cervical cancer, among the minimally invasive RH approaches, TLRH and LARVH, only TLRH approach was associated with worse PFS when compared with the TARH approach.